Steam pasteurization to reduce bacterial populations on commercially slaughtered beef carcasses - Schafer, D.E.; Kastner, Curtis L.; Phebus, Randall K.; Nutsch, Abbey L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
A steam pasteurization system (SPS) has been shown in laboratory and commercial evaluations to effectively reduce bacterial populations on freshly slaughtered beef. Our study evaluate d the bactericidal uniformity of SPS. Samples were collected from the five anatomical locations, one per carcass, 40 samples per location , so that 200 carcasses were evaluated before and 200 after pasteurization. Each carcass was sampled by wiping a 300 c m2 area of the specified location with a moist, sterile sponge. For all locations, the total aerobic plate count (APC) after pasteurization was lower (P#.01). Before pasteurization, the midline was contaminate d most heavily (2.5 log10 cfu/cm2 ). After pasteurization, the neck and midline had the highest residual APCs (1.3 and 1.1 log 10 cfu/cm2, respectively). For all anatomical locations, the enteric bacteria (E. coli, total coliform, an d Enterobacteriaceae ) were lower (P#.01) after than before pasteurization. Only two of 200 pasteurized carcasses ha d E. coli populations greater than 1 cfu/cm2. During pasteurization, steam blankets the carcasses, theoretically providing uniform bacterial destruction. This study demonstrated the effectiveness of SPS for reducing total aerobic and enteric bacterial populations uniformly over five anatomical locations on commercially processed carcasses.
Keywords: Beef; Beef carcasses; Antimicrobial treatment; Steam pasteurization